(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
The article presents the results of the study of the content of carotenoids of L. sulphureus mycelium under the action of LED lasers: BRP–3010–5, with red spectrum radiation with a wavelength of 635 nm, BBP–3010–5 with blue spectrum radiation with a wavelength of 405 nm and BGP–3010–5 with green spectrum radiation with a wavelength of 532 nm (irradiation energy 51.1 mJ/cm2) when cultured on nutrient medium with different concentrations of glucose. The irradiated mycelium served as a control. It was found that is most effective for the synthesis of carotenoids the use of glucose-peptone medium with a glucose concentration of 10 g/dm³ in combination with irradiation of mycelium with green light at a wavelength of 532 nm (irradiation energy 51.1 mJ/cm2). Under the action of this irradiation regime for strain L.s.-18 the content of carotenoids in the mycelium increased by 66.1% according to the control. Laser irradiation of mycelium with blue light with a wavelength of 405 nm (irradiation energy 51.1 mJ/cm2) increased the content of carotenoids for strain L.s.-18 by 46.7%. Irradiation with red light with a wavelength of 635 nm (irradiation energy 51.1 mJ/cm2) contributed to an increase in the content of carotenoids for strain L.s.-16 of the fungus L. sulphureus by 28.9%. It was found that the use of glucose-peptone medium with a glucose concentration of 8 g/dm3 in combination with irradiation of the mycelium with green light with a wavelength of 532 nm (irradiation energy 51.1 mJ/cm2) was less effective. Under these conditions, the content of carotenoids in the mycelium increased for strain L.s.-17 by 62.3%. Laser irradiation of mycelium with blue light with a wavelength of 405 nm (irradiation energy 51.1 mJ/cm2) increased the content of carotenoids for strain L.s.-17 by 30.6%. Irradiation with red light with a wavelength of 635 nm (irradiation energy 51.1 mJ/cm2) contributed to an increase in the content of carotenoids for strain L.s.-18 of the fungus L. sulphureus by 16.8% respectively. For strain L.s.-16 the number of carotenoids in the mycelium no increase. The use glucose-peptone medium with glucose concentrations of 6 and 4 g/dm3 in combination with laser irradiation of mycelium with red (wavelength 635 nm), blue (wavelength 405 nm) and green (wavelength 532 nm) light with irradiation energy 51.1 mJ/cm2 was no increase in the content of carotenoids in the mycelium.